Política estadual de agroecologia e produção orgânica do estado do Amazonas – convergências e contradições das políticas públicas para agricultura e meio ambiente - Santos, Tainá da Silva Rodrigues dos (Brasil, 2023)
Brazil has made important advances in terms of agroecology and organic production over the last 70 years. In the state of Amazonas, agroecological and organic movements emerged at the end of the 1990s. However, it was only in 2012, through articulations of non-governmental organizations and various social movements in the countryside, as well as traditional peoples and communities that pressured the State, was it institutionalized the National Policy for Agroecology and Organic Production (PNAPO), which provided an opportunity for the creation of state policies for agroecology and organic production. In Amazonas, the scenario of agroecology and organic production is positively marked by the articulations carried out by the Rede Maniva de Agroecologia (REMA) and the Organic Production Commission of Amazonas (CPOrg-AM), which resulted in the construction of the State Policy of Agroecology and Organic Production enacted in 2018. This research aimed to understand the scenarios and relationships in the construction process of PEAPO-AM, considering the state and federal conjunctures at the time. Information was obtained through a bibliographical survey, content analysis of the minutes of meetings and public hearings, and semi-structured interviews with key actors involved in the creation of the law and/or its unfolding. The interviews were transcribed and submitted to a discursive textual analysis, allowing the determination of the active movement of agroecology and organic production in the State of Amazonas.